1982
DOI: 10.1111/j.1432-1033.1982.tb05830.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain Clathrin: Studies of Its Ultrastructural Assemblies

Abstract: Clathrin p u r i h d to a high dzgrec of hoinogzncity showed thz presencz of accompanying polypzptidcs of lowsr molccular wcights and asscmblitd into baskcls or c a g a when thc pH of its solution was adjusted from pH 7.5 to 6.5. Brief chyinotrypsin treatment of this clathrin preparation at pH 6.5 cleaved clathrin-associated proteins rendzring clathrin unablc to rcform baskets. Hydrolysis of clathrin-associated proteins did not afYect clathrin's capacity to polymerize into open latticzs or to bind actin and a-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1982
1982
1987
1987

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…A characteristic of native clathrin is its ability to assemble into polygonal cage structures morphologically identical to those observed on coated vesicles. In all previous studies with clathrin heavy chains, the light chains were selectively removed by mild proteolysis using elastase (Kirchhausen and Harrison, 1981;Schmid et al, 1982) or chymotrypsin (Lisanti et al, 1981(Lisanti et al, , 1982a. Such heavy chains predominantly formed large irregular aggregates under standard reassembly conditions, suggesting that the light chains were required for the formation of proper cages.…”
Section: Discussionmentioning
confidence: 99%
“…A characteristic of native clathrin is its ability to assemble into polygonal cage structures morphologically identical to those observed on coated vesicles. In all previous studies with clathrin heavy chains, the light chains were selectively removed by mild proteolysis using elastase (Kirchhausen and Harrison, 1981;Schmid et al, 1982) or chymotrypsin (Lisanti et al, 1981(Lisanti et al, , 1982a. Such heavy chains predominantly formed large irregular aggregates under standard reassembly conditions, suggesting that the light chains were required for the formation of proper cages.…”
Section: Discussionmentioning
confidence: 99%
“…The demonstration of CAP2 phosphorylation offers exciting possibilities for the regulation of clathrin assembly/disassembly and coated vesicle-organellar interactions, since the CAPs are known to protrude from the surface of the coated vesicle (26) and may play a role in triskelion assembly/disassembly (27,28). The requirement for a nonvesicle-associated effector suggests that cytosolic components may be found that can produce the same effect as polylysine or histones and regulate phosphorylation of CAP2.…”
Section: Methodsmentioning
confidence: 99%
“…One of the substrates, pp50, is a component of the assembly polypeptide complex (Zaremba and Keen, 1985;Robinson and Pearse, 1986), which has a role in the formation of clathrin lattices. CAP2 is involved in the maintenance of the clathrin structure and in the interaction of clathrin with other proteins (Lisanti et al, 1982;Schmid and Rothman, 1985). The discovery of conditions resulting in phosphate incorporation into CAP2 prompted us to investigate the properties of the kinase(s) responsible for phosphorylating both pp50 and CAP2 and to define the enzyme(s) by their specific activation or inhibitors.…”
Section: Discussionmentioning
confidence: 99%